2003
DOI: 10.1016/s1359-6454(03)00209-x
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure development in hot-pressed silicon carbide: effects of aluminum, boron, and carbon additives

Abstract: Abstract:SiC was hot-pressed with aluminum, boron, and carbon additives. The Al content was modified either to obtain SiC samples containing a continuous Al gradient, or to vary the average Al content. In both cases, dramatic changes in microstructure, phase composition, and grain boundary structure were observed as a result of the Al variation.Similar processing and characterization were done with modified boron and carbon average contents. The systematic experiments allowed identification of the roles of Al,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 48 publications
0
37
0
1
Order By: Relevance
“…Chen et al [9][10][11] found that in addition to conferring good high-temperature creep and fatigue resistance, such heat treatments led to a ~20% increase in the room-temperature fracture toughness and fatigue-crack growth resistance (with no change in mechanism), compared to that in the as-hot-pressed material. However, an alternative approach is via microstructure modification through compositional changes, specifically by varying the aluminum content [15]. To date, several ABC-SiC materials have been processed with aluminum contents between 3 and 7 wt.%, where the changing Al additions resulted in significantly altered microstructures [7][8][9][10][11]15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chen et al [9][10][11] found that in addition to conferring good high-temperature creep and fatigue resistance, such heat treatments led to a ~20% increase in the room-temperature fracture toughness and fatigue-crack growth resistance (with no change in mechanism), compared to that in the as-hot-pressed material. However, an alternative approach is via microstructure modification through compositional changes, specifically by varying the aluminum content [15]. To date, several ABC-SiC materials have been processed with aluminum contents between 3 and 7 wt.%, where the changing Al additions resulted in significantly altered microstructures [7][8][9][10][11]15].…”
Section: Introductionmentioning
confidence: 99%
“…However, an alternative approach is via microstructure modification through compositional changes, specifically by varying the aluminum content [15]. To date, several ABC-SiC materials have been processed with aluminum contents between 3 and 7 wt.%, where the changing Al additions resulted in significantly altered microstructures [7][8][9][10][11]15]. Whereas the 3 wt.% material (3ABC) develops a microstructure of relatively uniform elongated grains with amorphous grain-boundary films (as noted above), a bimodal distribution of both elongated and equiaxed grains with partially crystallized grain-boundary films is seen in the 5ABC material, compared to principally equiaxed grains with only a few elongated (needle-like) grains, all with fully crystallized grain boundaries, in the 7ABC-SiC.…”
Section: Introductionmentioning
confidence: 99%
“…The joining temperature is chosen for the crystallizing of grain-boundary phase. 9) For comparison, another tape-like joining material starting from ¡-SiC powder was also used for the joining of SiC. As a result, we obtain nearly full dense SiC joints.…”
Section: Mechanical Properties Of Sic Jointsmentioning
confidence: 99%
“…7) It was demonstrated that SiC ceramics can be densified at temperatures lower than 1900°C with AlBC additives. The sintered SiC shows improved ambient-temperature fracture toughness and strength, 8), 9) and stable high-temperature toughness/creep behavior at temperatures up to 1300°C. 10) Effect of the forms of sintering additives in AlBC system, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Silicon carbide (SiC) is a brittle material with hardness of 22-35 GPa and fracture toughness of 2.96-5.8 MPa·m 1/2 [12,13]; SiC finds applications in the areas of protective system, space mirror, and abrasives [14][15][16]. β-SiAlON is relatively less brittle than α-SiC, with hardness of 14-17 GPa and fracture toughness of 6.5-7.88 MPa·m 1/2 [17,18]; β-SiAlON is one of the promising materials for cutting tools, turbine vanes and blades, and turbocharger rotors [19][20][21].…”
Section: Introductionmentioning
confidence: 99%